2015
DOI: 10.1080/03054985.2015.1023013
|View full text |Cite
|
Sign up to set email alerts
|

Teacher quality and school improvement: what is the role of research?

Abstract: In a rapidly changing world, students' success depends upon the schools' capacity to deal with their specific instructional needs. Thus, effective teaching plays the role of a unique protective factor that may reduce and even close the achievement gap. Two broad questions structure this study: What is the research contribution to teacher quality and improvement? What elements of teacher quality support school improvement? As one driver of school improvement, teacher quality is especially pertinent for underper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(65 citation statements)
references
References 43 publications
2
58
0
5
Order By: Relevance
“…That EIP can have positive benefits for both teachers and pupils has its roots in a growing evidence base. For example, correlational data reported by both Cordingley () and Mincu () suggest that where research is used as part of high‐quality initial teacher education and ongoing professional development, it is associated with higher teacher, school and system performance (similar relationships are reported in Sebba et al ., ; Godfrey, , ). CUREE (), meanwhile, lists a range of positive teacher outcomes that emerge from EIP including both improvements in pedagogic knowledge and skills, and greater teacher confidence.…”
Section: Perspectivesmentioning
confidence: 66%
“…That EIP can have positive benefits for both teachers and pupils has its roots in a growing evidence base. For example, correlational data reported by both Cordingley () and Mincu () suggest that where research is used as part of high‐quality initial teacher education and ongoing professional development, it is associated with higher teacher, school and system performance (similar relationships are reported in Sebba et al ., ; Godfrey, , ). CUREE (), meanwhile, lists a range of positive teacher outcomes that emerge from EIP including both improvements in pedagogic knowledge and skills, and greater teacher confidence.…”
Section: Perspectivesmentioning
confidence: 66%
“…However, this is specifically directed at minimal instruction approaches, such as discovery learning. Others moderate the binary 'direct instruction good, discovery learning bad' view, suggesting that evidence indicates that it is more effective to begin with direct instruction and the use of a wide range of pedagogies is desirable (Mincu 2015;Hattie 2009;Rowe 2006). Bandura's (1977) social learning theory goes some way to bridge the gap between the cognitive load (behaviourist) and the cognitive theories of learning, focusing on the role of observation by the learner; providing an insight into the early stages of a learner's engagement with new knew knowledge.…”
Section: Resultsmentioning
confidence: 99%
“…Kirschner, Sweller and Clark state that direct instruction (DI) enables the teacher to structure and guide learners in a manner that aids recall, transfer, application and problem solving. The implication being that DI should precede more learner-centric methods, such as discovery learning (Mincu 2015;Rowe 2006). Furthermore, Mincu cites Reynolds et al (2014) stating that constructivist approaches may be less appropriate learners who are younger, low-attaining or low socio-economic status.…”
Section: The 'Demonstration' and Cognitive Load Theorymentioning
confidence: 99%
“…Moreover, according to a past study conducted at 12 diverse Vocational education and Training sites around Australia by Burke and Smith (2009), they found that transformational leadership has positively impacted the independence and empowerment level of their school members. Furthermore, transformational leadership has also become one of the factors in triggering teachers' creativity and innovation during school transformation (Mincu, 2015).…”
Section: Transformational Leadershipmentioning
confidence: 99%